Credit Rationing and Financial Disorder - GUTTENTAG, JACK; HERRING, RICHARD (Journal of Finance, 1984)
ABSTRACT We develop a model of lender behavior in the presence of default risk and moral hazard that determines default premiums and identifies the conditions under which borrowers are rationed. A hypothesis regarding a cognitive bias in the formation of expectations provides a dynamic component to our analysis and allows us to explain how an economy becomes vulnerable to a financial crisis and why vulnerability may increase over time.